Whole person librarianship a social work approach to patron services - Zettervall, Sara K.; Nienow, Mary C. (Libraries Unlimited, 2019)
"Highlights the connections rapidly being made between librarians and social workers and explains how to create those partnerships"--Provided by publisher.